Personalized medicine for locally advanced rectal cancer: five years of complete clinical response after neoadjuvant radiochemotherapy—a case report with a literature review - Obonyo, Dennis; Uslar, Verena; Weyhe, Dirk; Tabriz, Navid (Frontiers in Surgery, 2024)
We present a case report of a 73-year-old male patient with a complete clinical response following neoadjuvant radiochemotherapy of mid-rectal adenocarcinoma. The patient was initially diagnosed with stage IIIB microsatellite stable mid-rectal adenocarcinoma in February 2017. During restaging in June 2017, which included rectoscopy, endosonography, computed tomography and magnetic resonance imaging, a complete clinical response was observed. After appropriate consultation, a watch-and-wait strategy was chosen. During stringent follow-up every 3 months for the first 3 years and thereafter every 6 months, no recurrence or regrowth was observed. After the fifth year of complete clinical response, we recommended an annual follow-up. As of November 2023, the patient has no signs of recurrence or late toxicity after radiochemotherapy. The omission of resection in patients with locally advanced rectal cancer and the establishment of a watch-and-wait strategy are currently under discussion as possible treatment courses in patients with complete clinical response. Long-term data on watch-and-wait strategies for patients with a complete clinical response in locally advanced rectal cancer are rare. A clear national and international accepted standardization of follow-up programs for patients managed by a watch-and-wait strategy in the long-term is missing. Here, we report the case of a patient with stage IIIB rectal cancer who had undergone a follow-up program for more than five years and discuss the current literature. Our case report and literature review highlights that a watch-and-wait strategy does not seem to increase the risk of systemic disease or compromise survival outcomes in selected locally advanced rectal cancer patients. Thus, our case contributes to the growing body of knowledge on personalized and precision medicine for rectal cancer.